Equality of chances in the context of inclusive education in Romania. Case study - Alina Gabriela Anghel (Association of Social and Educational Innovation, 2017)
Inclusive education in Romania is realized if the principle of equality of chances for all children is respected. In this framework, a series of measures and strategies specific of an educational process centered on the student and on his special educational needs have been designed and implemented. The educational policies in Romania promote and implement equal access to education for all children with no discrimination. For this, the integrated approach for the problems of the child with special educative demands in the context of a multisectorial and pluridisciplinary intervention will successfully assure a high-quality education for people with special educative demands.